Relationship between overexpression of ras p21 oncoprotein and K-ras codon 12 and 13 mutations in Turkish colorectal cancer patients - (:unkn) unknown (AVES, 2008)
Background/aims: The activation of ras family genes plays an important role in colorectal tumorigenesis. We investigated the clinicopathological characteristics and point mutations of K-ras oncogene codons 12/13 and ras p21 expression using paraffin-embedded materials from cancerous and the surrounding normal tissues of 53 colorectal cancer cases. Methods; K-ras codons 12 and 13 point mutations were analyzed by PCR-Single-Strand Conformational Polymorphism (SSCP) and followed by DNA sequencing, while ras p21 expression was evaluated using immunohistochemistry. Results: Mutations of K-ras and overexpression of the ras p21 were detected in 11% and 76% of the tumors, respectively. Ras protein level in tumor was increased an average of 4.6-fold over that of normal mucosa. Ras p21 overexpression did not correlate with any of the clinicopathological parameters examined. K-ras gene mutations were found mostly in the presence of a mucinous component within the tumor (p=0.06). Follow-up data were available for 43 patients. There was no statistically significant correlation between these alterations and patient outcomes. Conclusions: Our data suggest that.. apart from K-ras codons 12/13 point mutations, overexpression of the ras family genes is important in the development of the disease but it appears not to be predictive of survival. Furthermore, mucinous secretion in the colorectum may represent a distinct genetic pattern.
Keywords: colorectal cancer; ras p21 overexpression; K-ras point mutations; survival; GENE-MUTATIONS; PROGNOSTIC-FACTORS; COLON-CANCER; LIFE-STYLE; P53; EXPRESSION; CARCINOMA; DNA; METASTASES; ONCOGENES